Social Media Digital Strategy for Coffee Business at Cafeteria Universitas Islam Al-Azhar - Muhammad Khairul Tamimi; Yasman Pirdaus; M. Hasan Amir Husen (Universitas Islam Al-Azhar Mataram, 2025)
Marketing is one of the important elements in the development of micro, small, and medium enterprises (MSMEs). In practice, marketing strategies can be implemented through various media such as social media, promotional videos, and websites. These strategies play a role in expanding consumer reach and increasing product competitiveness in the market. One example of the application of this marketing strategy is at Café Taria Unizar, a culinary business unit located in the Al-Azhar Islamic University (Unizar) environment, which provides various kinds of food and drinks for students. The products sold at Café Taria Unizar include meatballs, soto, bread, snacks, and various drinks. In addition, this cafe also collaborates with tenants or supplier partners who provide goods such as rice, tofu, and other foods. Currently, product marketing at Café Taria uses social media Instagram, TikTok, Facebook, etc. as a means of promotion. Café Taria Unizar was officially established on August 10, 2024 and has great opportunities to grow through the implementation of more innovative and structured digital marketing strategies. Implementing the right marketing strategy can be the key to increasing the number of customers and strengthening Café Taria Unizar as a productive and sustainable business unit in the campus environment..